Simultaneous exfoliation and functionalization of hexagonal boron nitride in the aqueous phase for the synthesis of high-performance wastewater treatment membrane. (10th September 2021) - Keshebo, Degu Lere; Hu, Chien-Chieh; Hung, Wei-Song; Wang, Chih-Feng; Tsai, Hsieh-Chih; Lee, Kueir-Rarn; Lai, Juin-Yih
Abstract: A highly permselective membrane is needed for environmental applications due to current industrialization and environmental constraints. However, membrane fouling and firmness problems are encountered during operation in harsh working environments. Hexagonal boron nitride is an encouraging material due to its solidity under various working conditions, but exfoliation using environmentally friendly techniques is challenging. In this study, aqueous-phase exfoliation using tannic acid was demonstrated to be an easy, novel, and green method for preparing functionalized two-dimensional hexagonal boron nitride nanosheets. Microscopic and spectroscopic techniques were used to characterize the exfoliated nanosheets and the synthesized membrane. Tannic acid is adsorbed on the hexagonal boron nitride surface and gradually exfoliates the hexagonal boron nitride to release a few layers of functionalized boron nitride nanosheets; it behaves as a green surfactant by weakening the interlayer interactions. Ultimately, the functionalized exfoliated nanosheets are used to prepare a membrane for environmental applications. Fascinatingly, the prepared membrane is exceedingly stable in water and organic solvents and manifests adequate efficiency in transporting solvents with excellent screening of solutes and long-term antifouling performance. The synthesized membrane's rapid transport of solvents and ample separation efficiency of solutes may be due to the robust nanochannel and thin laminar networks of the nanosheets, which endow the membrane with favorable properties for separation and decontamination developments. Graphical abstract: Image 1 Highlights: Aqueous exfoliation and tannic acid functionalization of h-BN nanosheets. High solutes rejection with high flux membrane and high antifouling for log-term filtration. Multifunctional membrane for both industrial and municipal wastewater.